1258Development of a valid evaluation tool assessing health behaviours among Māori & Pasifika young people. (2nd September 2021) - Hardt, Jessica; Cooper, Ellen; MacMillan, Freya; Brignano, Sebastien; Kira, Kirstine; Santos, Daphne; Thompson, Rhonda; Simmons, Distinguished David; McBride, Kate
Abstract: Background: The Māori & Pasifika population experience high rates of health inequity, with a greater prevalence of obesity and the associated, life diminishing comorbidities. This is in part attributable to higher socioeconomic disadvantage, low health literacy and a lack of culturally tailored health services. Currently no validated tool exists to assess health behaviour change among Māori & Pasifika populations or success of tailored health interventions to tackle chronic disease. Methods: The project incorporates a comprehensive validation and pilot testing process, including 1) cognitive interviewing and 2) test-retest reproducibility. Participants will include a representative sample of Māori & Pasifika young people and their parents/guardians. All research methodology is guided by cultural experts, specific to the Māori & Pasifika population. Results: Qualitative data collected via cognitive interviewing will provide feedback regarding the readability, comprehension and content validity of the questionnaire items. Thematic analysis will inform improvements, optimising participant understandability. Cronbach's alpha will be used to assess internal consistency and Pearson's r will determine questionnaire test-retest reproducibility. Conclusions: A validated questionnaire articulating with cultural values will provide meaningful data to researchers, health practitioners and government bodies regarding the lifestyle decisions of Māori & Pasifika peoples. Enhanced monitoring will determine the success of health initiatives to improve health outcomes of a priority population, across Australia and internationally. Key messages: Lifestyle programs aiming to improve health outcomes are increasingly adapted to incorporate and acknowledge cultural values. Reliable measurement tools, including questionnaires, are fundamental to advancing future health research and tackling health inequity among priority populations.